Silage production from the residues of plantain (Musa AAB Simmonds): a nutritional analysis through process simulation - Gómez, James A. (2020)
Sustainable processes are required to decrease the environmental and economic impact of residues and wastes. Therefore, the agro-industrial waste upcycling, as substitutes of substrate, is of paramount relevance. In this work, the nutritional value of silage from fresh residues of plantain agroindustry was evaluated by process simulation, as an alternative of dairy cattle feed. Several databases were accessed to design the process. SuperPro Designer V10 simulator was used. Results showed that fresh plantain residues mixed with 97.14% pseudo total, 0.24% rejection banana and 1.63% of rachis are not recommended for dairy cattle consumption due to its high moisture content (>90%), fiber neutral detergent (>50%) and acid detergent fiber (>30%). Simulation techniques have shown to be a powerful tool when making decisions on investment projects that involve technologies for waste utilization in order to find the more appropriate process configuration reducing experimentation requirements.